Efficient Therapeutic Function and Mechanisms of Human Polyclonal CD8+CD103+Foxp3+ Regulatory T Cells on Collagen-Induced Arthritis in Mice - Juan Sun; Yiming Yang; Xiaona Huo; Beibei Zhu; Zhenhua Li; Xueyu Jiang; Rufeng Xie; Li Gao; Ying Sun; Huahua Fan; Yongming Zhu; Jie Yang (Journal of Immunology Research)
Objective. To investigate the potential therapeutic effect in a rheumatoid arthritis model of stable human CD8+ regulatory T cells (hCD8+Tregs) induced by TGF-β1 and rapamycin (RAPA) in vitro. Methods. Human CD8+T cells were isolated from human peripheral blood mononuclear cells and induced/expanded with TGF-β1 and RAPA along with anti-CD3/28 beads and IL-2 in vitro and harvested as hCD8+Tregs. The phenotypes, suppressive characteristics, and stability of the hCD8+Tregs in an inflammatory microenvironment were examined in vitro. Human CD8+Tregs were transfused into an acollagen-induced arthritis (CIA) mouse model, and their therapeutic effects and related mechanisms were investigated. Results. Human CD8+Tregs induced by TGF-β1/RAPA showed high expression of Foxp3 and CD103, exhibited vigorous suppression ability, and were stable in inflammatory microenvironments. In CIA mice, the clinical scores, levels of anti-collagen IgG antibody, and cartilage destruction were significantly reduced after adoptive transfusion with hCD8+Tregs. Moreover, hCD8+Treg treatment significantly reduced the number of Th17 cells, increased the number of CD4+IFN-γ+T cells, and produced self CD4+Foxp3+Tregs in vivo. In an in vitro cell coculture assay, hCD8+Tregs significantly inhibited mouse CD4+ effector T cell proliferation, induced mouse CD4+Foxp3+Treg and CD4+IFN-γ+Th1 cell production, reduced Th17 cell development, and downregulated CD80/86 expression on mature DCs (mDCs). Conclusion. TGF-β1/RAPA can induce hCD8+Tregs with stable suppressive characteristics, which could significantly alleviate the severity of CIA based on their stable suppressive ability in an inflammatory microenvironment and further influence the function of other downstream cell subtypes. Human CD8+Tregs might be a therapeutic strategy for rheumatoid arthritis.